What Drives Employee Engagement: Personal Attributes Or Organisational Climate? - Baldev R. Sharma and Sombala Ningthoujam (Abhigyan, 2013)
Employee engagement has been described as a key to an organisation’s success and competitiveness. Both practitioners and academics tend to agree that the consequences of employee engagement are positive (Saks, 2006). With the help of a purposive sample of 50 managerial employees from a public sector organisation, the study on which this paper is based attempts to identify the predictors of employee engagement. Between the two dimensions of engagement, job engagement was found to score slightly higher (68.73 percent) than organisation engagement (64.47 percent). Further analysis of data revealed that while both personal attributes and organizational climate are relevant as predictors of engagement, the former are found to be more important than the latter. The limitations of the study are acknowledged and some suggestions are made for future research.